Breaking the links between conflict and hunger in Africa - Messer, Ellen; Cohen, Marc J. (International Food Policy Research Institute, 2004)
Armed conflicts frequently lead to the destruction of food systems. Often, warring parties manipulate starvation as a deliberate tactic, using their control over access to food to attract and reward friends and humble and punish enemies. Such conflicts are “food wars,” not only because hunger is used as a weapon but also because food insecurity is both an effect and cause of conflict....National governments in Africa, together with global investors, whether private or public (aid donors), must include conflict-prevention considerations in the planning, implementation, and evaluation of development programs and projects.They should calculate savings from conflict avoidance as part of the returns to development spending. Such an approach can help break the links between conflict and food insecurity. -- from Text